Intermediaries' perspectives on the public's role in the energy transitions needed to deliver UK climate change policy goals. (May 2018) - Shaw, Christopher; Hurth, Victoria; Capstick, Stuart; Cox, Emily
Abstract: There is now a large body of research into public understanding of climate change and energy challenges. There is however little empirical examination of how actors from politics, government, civil society and non-governmental organisations regard the role of public engagement in climate and energy policy. Research is lacking as to their views on the desirability of active citizen participation or indeed whether they draw on the findings from social science research in forming strategies and policy. This paper presents an analysis of interviews with policy experts and deliberative seminars held with non-governmental stakeholders acting in an intermediary capacity between climate policy and the public. A comparison of four policy scenarios was used to explore intermediaries' beliefs about the role of the public in delivering the UK's Climate Change Act targets. The results reveal a general antipathy to policies that seek to 'engage' the public and a lack of knowledge amongst seminar participants about how insights from the social sciences can be used to build and sustain public engagement. This research exposes the need to assess the means by which public engagement can better be understood, integrated and most effectively utilised for sustainable progression towards climate targets. Highlights: Public engagement long argued to be key to delivery of climate policy goals. Participants in this research do not see public engagement as necessary or desirable. Positive public engagement anticipated to be difficult to build and sustain. There was little awareness of the social sciences research into building public engagement. New ways of sharing research in this field with intermediaries is important to build public engagement.